Economic development in twentieth century East Asia : the international context - Ikeo, Aiko, 1956- (Routledge, 1997)
This collection supplies fascinating insights into aspects of East Asian economic development. It will interest scholars in a variety of related fields and provoke further research and debate.
Keywords: East Asia -- Economic conditions -- Congresses.; East Asia -- Foreign economic relations -- Congresses.; Extrême-Orient -- Conditions économiques -- Congrès.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; Economic history; International economic relations; East Asia; Electronic books.; Conference papers and proceedings